Effectivity of various concentration of lactose in Tris extender on liquid semen viability of Saanen bucks - Surya Natal Tambing; I-K Sutama; R.I Arifiantini (Indonesian Center for Animal Research and Development (ICARD), 2003)
The objective of this study is to determine the best concentration of lactose in Tris extender in maintaining liquid semen viability of Saanen bucks stored at 5°C. Four heads of Saanen bucks of 2-4 years old were used as semen source. Semen was collected once a week using an artificial vagina. Variance analysis was conducted based on completely randomized design with three treatments, i.e 30, 60, and 90 mM lactose (L30, L68 and L90). Duncan test was used to observe the different between treatment. Results indicated that the mean percentage of motility, live sperm, intact plasma membrane, and intact acrosomal cap of liquid semen in treatment L30 (70.83; 78.20; 79.56 and 81.20% respectively) were significantly higher (P<0.05) than treatment L60 (67.08; 73.73; 75.01 and 76.87% respectively) and treatment L90 (61.50; 71.88; 69.08 and 71.33% respectively). After storage for 48 hours at 5°C apparently the mean percentage of motility, live sperm, intact plasma membrane and intact acrosomal cap in treatment L30 were significantly higher (P<0.05) than those of in treatment L60 and L90. Decreasing percentage of motility, live sperm, intact plasma membrane, and intact acrosomal cap during storage at 50C from 0 until 48 hour in treatment L30 (42.83; 19.75; 40.84 and 39.00% respectively) were significantly lower (P<0.05) than those of in treatment L60 (55.41; 23.06; 50.14; and 50.90% respectively) and treatment L90 (54.83; 29.93; 50.14 and 50.97% respectively). It was concluded that supplementation 30 mM lactose in Tris extender could maintain liquid semen viability in Saanen bucks. Key words: Saanen bucks, lactose, liquid semen